Child abuse among working children in rural Bangladesh: prevalence and determinants - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2020)
The paper aims to improve our understanding about the prevalence and determinants of child abuse in rural Bangladesh. Data from the 1995 sample survey of 4,643 children aged 10-15 years in 150 villages were used. Findings revealed that 21% of the children were in the labour force although the Bangladeshi laws prohibited child labour. The prevalence of child abuse and exploitation was widespread in Bangladeshi villages as 2.3% of all children were physically abused, 2% were financially exploited, l.7% were forced to involve in inappropriate activities, and 3% were forced to work for long hours. The prevalence of physical assault was much higher among younger children although the probability of other types of abuse was higher among older children. Boys were more exposed than girls to be abused of any kind. Poverty was also significantly associated with child abuse. Multivariate analysis suggested that the out-of-school children and the children of illiterate, landless and unskilled labourers were more likely to be abused than others when age and sex of children were controlled. The paper concludes that raising public awareness against child abuse and promoting preventive measures should be adopted to reduce child abuse in Bangladesh.